Addendum to "Relationships between Authentic Leadership, Moral Courage, and Ethical and Pro-Social Behaviors". Issue 2 (April 2014) - Hannah, Sean T.; Avolio, Bruce J.; Walumbwa, Fred O.
ABSTRACT: The authors provide this addendum to the following article to provide corrections to the results reported and further explanation of the structural equation modeling techniques utilized: Sean T. Hannah, Bruce J. Avolio, and Fred O. Walumbwa, "The Relationships between Authentic Leadership, Moral Courage, and Ethical and Pro-Social Behaviors, " Business Ethics Quarterly 21:4 (October 2011): 555–78.